Humanitarian Culture of a Teacher in The System of Professional Education - Lyudmila Anatol'yevna SEMENOVA1; Lyudmila Ivanovna KONOVALOVA; Natalia Vladimirovna BREDIKHINA1 (Communications of International Proceedings, 2020)
It follows from the current trends in the development of society that the current educational practice of professional training, aimed at transferring the maximum amount of knowledge, has lost its relevance. Accordingly, the formation of a new paradigm of training a competitive specialist, aimed at creating conditions for the formation and education of graduates of professional educational institutions, able to optimally dispose of the knowledge obtained, effectively self-realized, be in demand by society-the result of a conscious need. This determines the relevance of the presented work. The purpose of the article is to theoretically justify the need to overcome the value neutrality in the field of methods and technology of training a competitive specialist through the humanitarian culture of the teacher and the formation of the educational environment of the OU. The main research methods in the work are such General logical methods as: analysis, analogy, generalization.
Keywords: teacher's humanitarian culture; educational environment; professional training; overcoming value neutrality; cognitive value of fiction.